A Self-adaptive System reconfiguring a Composite Web Service for Emergency Medical Aid - Kahlon, Navinderjit Kaur (International Journal of Computer Sciences and Engineering, 2019)
The web services run in a highly dynamic environment so, the most fundamental challenges in web services based software solutions is to manage QoS changes of their component web services at runtime. In order to make the composite web service adapt to these changes, a self adaptive system is proposed for web service composition. The distributed approach is followed at the client and the server side along with the runtime monitoring and adaptation of the component web services at the provider side. For the self adaptive systems to recover as quickly as possible, a way of performance prediction is proposed in this paper along with the case study and the performance of the system. The prototype is developed using Java, and the JADE platform is used for implementing software agents using hospital lookup case study. The experimental results show that the proposed solution has better performance for supporting self adaptive web service composition.